Analysis of Mathematical Logic Intelligence of Children Aged 4-5 Years at KB Scholar Bapangan in Terms of the Application of Outing Class Learning Methods - Utami, Nurulita Tri; Zulfahmi, Muhammad Nofan (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2024)
This study focuses on an in-depth exploration of the influence of the